Radio and Cinema in the Making of a Divided Argentina - Kelly Hopfenblatt, Alejandro (Imagofagia, 2021)
Sobre Karush, Matthew B. Culture of Class: Radio and Cinema in the Making of a Divided Argentina, 1920-1946. Durham: Duke UP, 2012, 288 pp., ISBN 978-0822352648.